“The System Is So Messed up”: Neutrality and Efficiency in an Eviction Courtroom - Jacob Scott Kepes; Alex M. Kempler (Socius)
Eviction research focuses primarily on what happens before or after an eviction, overlooking the importance of the courtroom in understanding how the eviction process unfolds. We offer a case study of an eviction court in Franklin County, Ohio, during the height of the COVID-19 pandemic. Using ethnographic observation and qualitative interviews, we investigate the following questions: (1) What role do courtroom actors play in eviction procedures? and (2) How have the COVID-19 pandemic and pandemic-related policy impacted courtroom processes? We highlight this court’s determination to continue business as usual, as demonstrated through allegiance to the logics of neutrality and efficiency. Although the court was able to implement small-scale changes, these changes were made in the interest of landlords, ultimately undermining the court’s supposed neutrality and enforcing a type of efficiency that favored the continued processing of cases despite warnings from public health officials.